(untitled) (Journal of the College of Basic Education, 2024)
The recent decades have witnessed tremendous development in several technical fields, including the field of printing techniques and raw materials, and this development came as a result of the rapid scientific and technical progress; Today, it has become difficult to compare traditional printing techniques with modern printing techniques, which have a role in producing print advertising, As the advertising designer can meet the advertiser’s requirements as quickly as possible and with the least effort, this is due to the technical development in the field of printing, and modern printing techniques have an impact on the final output of the advertisement, which leads to achieving impact and response to the recipient, It became possible to choose the type of printing suitable for each stamp surface, and in a way that suits the advertisement to be printed. There are many different advertisements, including street and building advertisements, as well as indoor advertisements. Therefore, it requires choosing the type of printing, materials, and the extent of their resistance to climate variables, as well as the use of inks. With bright colors, it enhances attracting and grabbing the attention of the recipient, which arouses his interest as soon as possible, in addition to the way the advertisement is presented and its location, all of which have an effect on changing the behavior of the recipientزTherefore, a problem can be identified by asking the following: - What is the relationship between modern printing techniques and the effect on the recipient and his response to the print advertisement? The study included four chapters, as the first chapter discussed the research problem and its importance, and the study aimed to (discover the impact and response achieved by modern printing techniques in printed advertising). The limits of the research were represented by modern printing techniques and their relationship to the impact and response in the printed advertisement, and the research time limits were from 1/1/2021 to 30/6/2021, and the spatial limits were (advertisements displayed in the city of Baghdad / Rusafa side) as well as specifying The search terms mentioned in the study title